Formation of plasma technological influence of vacuum arc on the internal surfaces of metal pipes and putting of the protecting coatings - Arustamov, V.N.; Ashurov, Kh.B.; Kadirov, Kh.Kh.; Khudaykulov, I.Kh. (International Conference on Plasma Surface Engineering, 2013)
In many cases of industrial applications it is economically profitable or technically necessary to combine bulk features of one material with surface features of another one in a single material. Vacuum-arc treatment of products from inexpensive materials to form new required features of surface layers is more perspective owing to its unlimited feasibility in process efficiency. Pipes are in great demand in oil-gas industries and power engineering. But there are no effective methods for pipe inner surface treatment and pipe coating deposition, which makes it impossible to use inexpensive steel pipes under conditions of aggressive liquids, high temperature, high pressure and other parameters leading to oxidation, erosion and pipe life. Therefore, development of plasma-arc technologies of pipe inner surface treatment and pipe coating deposition is very topical and actual. A specific effect of vacuum-arc discharge on material surface is due to high concentration of energy in a chaotically rapidly moving cathode spot, short-term local heating of surface and its rapid cooling. The technological effect of cathode plasma on surface is based on cathode spot movement. The effect of a plasma flow of cathode spots formed on the outer surface of a pipe cathode and controlled by a system of vacuum-arc cathode spot fixation with magnets placed inside an electrode has been considered. A great number of studies have been devoted to explaining and investigating “anomalous” movement of the cathode spots. It has been shown that the cathode spot moves in the direction of the greatest action of discharge’s own magnetic field and outer magnetic field. The magnets initiate an arc magnetic field that confines the cathode spots and makes it possible to scan (control) them on the electrode-cathode surface and act with a plasma flow and deposit coats on inner surface of a coaxially placed pipe-product. The high efficiency of the plasma vacuum-arc method for pipe inner surface treatment and coat deposition has been found.